Wacana Perempuan Dalam Teks Berita Kasus Kekerasan Seksual Anak di Portal Berita Grid.Id Periode Agustus 2020 - Solihah, Ananda Mar'attus; Candrasari, Yuli (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
Sexual violence cases is one of never ending cases that happens every year. Generally the victim of violence cases are woman. As a news portal that have characteristic with a point of view of woman, Grid.ID is interesting to be explored deeper about how Grid.ID will discuss about woman in a child sexual violence. Method that used by researchers in this research is Sara Mills discourse analysis that sees how position of the subjects and the writer-reader. Researcher takes the news that becomes research corpus for further analysis. The analysis results shows that in news text discourse about child sexual violence, woman is in a position as an object. Woman characteristic described as the flow of patriarchal discourse, which is considered as passive, weak, and dependent on men. While when telling the male perpetrators in cases of sexual violence against children in Grid.ID, there are still some words that defense to the perpetrators. Keywords: Sara Mills Discourse